Validation: Work assessment scale and interprofessional communication in simulated practice - Conti Machado, Giovanna Cristina; Guimarães dos Santos Almeida, Rodrigo; Kayzuka Cotta Filho, Cezar; Yukio Mano, Leandro; Raniere de Oliveira Costa, Raphael; Mazzo, Alessandra (O Mundo da Saúde, 2022)
Interprofessional work revolutionizes the model of health education and practice, and requires effective communication between team members. However, although it has been discussed for more than three decades, its introduction into health courses is still a challenge. To overcome such barriers, the use of clinical simulations allows for the insertion of and reflection on issues within the real practical context. The incorporation of instruments that guide the skills necessary for interprofessional work into the work of facilitators, such as the “Performance Assessment Tools for Interprofessional Communication and Teamwork – Novice” (PACT–Novice), is essential. Thus, this study aimed to translate and validate the construct’s content and verify the reliability of the Brazilian version of the PACT-Novice instrument in a simulated context, among students in Brazil. This is a methodological study of translation, cultural adaptation, and validation of content and reliability of the instrument, divided into Phase A - Translation and cultural validation and Phase B - Validation and reliability of the instrument. In Phase A), after analyzing the judges’ assessments of the translated version, the final version of the PACT-Students instrument was reached, with a CVI index of 95.0% for all items. For Phase B, the analysis of the set of items that make up the PACT-Students and their relationship with the construct resulted in a Cronbach’s Alpha of 0.891. The process of translation and validation of the PACT-Students instrument was efficient, demonstrating high reliability for its application. However, further studies are suggested to reinforce the results obtained.